Graft Copolymerization of Acrylonitrile and Ethyl Acrylate onto Pinus Roxburghii Wood Surface Enhanced Physicochemical Properties and Antibacterial Activity - Gaurav Sharma; Amit Kumar; Mu. Naushad; Fahad A. Al-Misned; Hamed A. El-Serehy; Ayman A. Ghfar; Kulwant Rai Sharma; Chuanling Si; Florian J. Stadler (Journal of Chemistry)
As a natural and the most abundant material, wood was used as a scaffold for the grafting of acrylonitrile (AN) and ethyl acrylate (EA) to develop a novel grafted wood. Thus, chemical modification of the wood was carried out by means of grafting. It is clear from the characterization techniques (FTIR, SEM, and XRD) that grafting of acrylonitrile (AN) and ethyl acrylate (EA) was successfully performed on the Pinus roxburghii wood. Monomer and initiator concentration, temperature, time, and pH parameters have been varied to obtain the maximum percent grafting yield. A significant influence was observed on the physicochemical properties, morphological structure, and bacterial resistant nature after the graft copolymerization of AN + EA on the raw wood. This approach of grafting of wood would lead to the construction of a new class of materials with better properties and will also promote innovative consumption of renewable wood.